2022
DOI: 10.3390/ijms232416051
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in Multiple Transcriptomic Endometrial Pathways Is Associated with Recurrent Implantation Failure and Recurrent Early Pregnancy Loss

Abstract: Overlapping disease aetiologies associated with multiple altered biological processes have been identified that change the endometrial function leading to recurrent implantation failure (RIF) and recurrent early pregnancy loss (REPL). We aimed to provide a detailed insight into the nature of the biological malfunction and related pathways of differentially expressed genes in RIF and REPL. Endometrial biopsies were obtained from 9 women experiencing RIF, REPL and control groups. Affymetrix microarray analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…GO analysis demonstrated that DEGs in RIF were primarily enriched in lipid metabolism and immune processes. In KEGG analysis, the NF-κB, TNF, and adipocytokine signaling pathways were linked together, which is consistet with similar RIF studies showing dysregulated NF-κB and TNF pathways [ 24 , 38 , 39 , 40 ]. GSEA results demonstrated that RIF was significantly enriched in downregulated graft-versus-host disease, allograft rejection, complement and coagulation cascades, antigen processing and presentation, upregulated fatty acid biosynthesis, ovarian steroidogenesis, and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 62%
“…GO analysis demonstrated that DEGs in RIF were primarily enriched in lipid metabolism and immune processes. In KEGG analysis, the NF-κB, TNF, and adipocytokine signaling pathways were linked together, which is consistet with similar RIF studies showing dysregulated NF-κB and TNF pathways [ 24 , 38 , 39 , 40 ]. GSEA results demonstrated that RIF was significantly enriched in downregulated graft-versus-host disease, allograft rejection, complement and coagulation cascades, antigen processing and presentation, upregulated fatty acid biosynthesis, ovarian steroidogenesis, and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 62%
“…All women who did not actually undergo a fresh embryo transfer during that cycle ( n = 13) or had a biochemical or clinical pregnancy loss ( n = 9), were excluded from this analysis. The latter were excluded as women with a pregnancy loss may have a different endometrial transcriptome profile from women who had not been able to get pregnant 24 …”
Section: Methodsmentioning
confidence: 99%
“…The latter were excluded as women with a pregnancy loss may have a different endometrial transcriptome profile from women who had not been able to get pregnant. 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarify the differentially expressed genes related downregulation pathways of RM and recurrent implantation failure. [27] We hypothesize that this gene regulates the disease process by participating in these 2 signaling pathways. Multiple connexin proteins are expressed in human tissues, including GJA1, commonly referred to as connexin 43 due to its molecular weight in thousands of daltons, forms GJA1 = connexin 43s and dominates in the decidua and trophoblast.…”
Section: Gene Namementioning
confidence: 99%